2017
DOI: 10.1111/1750-3841.13843
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Escherichia coli O157:H7, Salmonella enteritidis, and Listeria monocytogenes at a Very Low Level Using Simultaneous Enrichment Broth and Multichannel SPR Biosensor

Abstract: Our method is expected as a rapid and simultaneous detection method for pathogens at very low levels. It has great potential for safety control of food and microbiological detection applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Recently, Zhang et al developed a multichannel SPR‐based biosensor for detection of E. coli O157:H7 simultaneously with other two vital food‐borne pathogens: L. monocytogenes and S. enteritidis . The biosensor was able to detect 14, 28, and 6 CFU/mL of E. coli O157:H7, L. monocytogenes , and S. enteritidis , respectively .…”
Section: Medical Applications Of Biosensorsmentioning
confidence: 99%
“…Recently, Zhang et al developed a multichannel SPR‐based biosensor for detection of E. coli O157:H7 simultaneously with other two vital food‐borne pathogens: L. monocytogenes and S. enteritidis . The biosensor was able to detect 14, 28, and 6 CFU/mL of E. coli O157:H7, L. monocytogenes , and S. enteritidis , respectively .…”
Section: Medical Applications Of Biosensorsmentioning
confidence: 99%
“…Rapid pathogenic bacterial diagnosis has been applied to conduct measurements in biological and food matrix [3]. Up to date, different method has been applied by several research group for enumeration of pathogenic bacteriaespecially L. monocytogenes using polymerase chain reaction immunoassay [4,5], electrochemical sensors [6][7][8], bioluminescence [9,10], DNA-based sensors [11,12], ELISA [13,14], surface plasmon resonance [15,16], fluorescence [17,18], surface-enhanced Raman scattering (SERS) [19][20][21]. It was indicated that the reported methods were optimized to select proper system usage to obtain selectivity and precision, there were some problems such as poor sensitivity and long experimental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…; and result in high economic losses and considerable mortality of contaminated consumers, such as Escherichia coli. Thus, identifying these microorganisms is important to evaluate the quality of food and prevent food outbreaks (ZHANG et al, 2017). In this context, meat products require especial care because of their potential to carry foodborne pathogens, especially when undergo intense handling (SHAWISH; TARABEES, 2017).…”
Section: Introductionmentioning
confidence: 99%